Open resections for congenital lung malformations - Mullassery Dhanya; Jones Matthew (Wolters Kluwer Medknow Publications, 2008)
Aim: Pediatric lung resection is a relatively uncommon procedure that is usually performed for congenital lesions. In recent years, thoracoscopic resection has become increasingly popular, particularly for small peripheral lesions. The aim of this study was to review our experience with traditional open lung resection in order to evaluate the existing "gold standard." Materials and Methods: We carried out a retrospective analysis of all children having lung resection for congenital lesions at our institution between 1997 and 2004. Data were collected from analysis of case notes, operative records and clinical consultation. The mean follow-up was 37.95 months. The data were analyzed using SPSS. Results: Forty-one children (13 F/28 M) underwent major lung resections during the study period. Their median age was 4.66 months (1 day-9 years). The resected lesions included 21 congenital cystic adenomatoid malformations, 14 congenital lobar emphysema, four sequestrations and one bronchogenic cyst. Fifty percent of the lesions were diagnosed antenatally. Twenty-six patients had a complete lobectomy while 15 patients had parenchymal sparing resection of the lesion alone. Mean postoperative stay was 5.7 days. There have been no complications in any of the patients. All patients are currently alive, asymptomatic and well. None of the patients have any significant chest deformity. Conclusions: We conclude that open lung resection enables parenchymal sparing surgery, is versatile, has few complications and produces very good long-term results. It remains the "gold standard" against which minimally invasive techniques may be judged.